A Review of the Regional Court Decision Regarding the Exemption of Temporary Protected Status Holders in Türkiye from Cautio Judicatum Solvi - Cemre Tüysüz (Public and Private International Law Bulletin)
For some cases with a foreign element, the obligation of cautio judicatum solvi before applying to the courts has been accepted into Turkish law. The subject of this review mainly focuses on the exemption from cautio judicatum solvi for foreigners when they apply to courts and enforcement offices. Due to the developments and events in the Syrian Arab Republic over the past years, millions of Syrian citizens have crossed the borders and entered Türkiye. Because they are unable to return home due to the ongoing events in Syria and thus the need exists for establishing a legal framework regarding their presence in Türkiye, temporary protected status has been accepted into Turkish Law through the Code on Foreigners and International Protection (Law No. 6458). This review focuses on a decision rendered by the 3rd Civil Chamber of the Adana Regional Court regarding the applicability of the exemption rule in the 1951 Refugee Convention to citizen refugees from the Syrian Arab Republic. The decision rendered by the 3rd Civil Chamber of the Adana RegionalCourt accepts the application of the 1951 Refugee Convention to those holding temporary protected status and has declared them to be exempt from cautio judicatum solvi, as Turkish legislation lacks any such regulation. While reviewing this decision, the study will consider the scope and aim of cautio judicatum solvi in Turkish law, as well as the possibilities for exemption from such an obligation. The study will also examine the view in Turkish law toward refugees and those holding temporary protected status through the Code on Foreigners and International Protection and other such relevant regulations.